The Impact of e-Service Quality on e-Satisfaction and Loyalty in BTN Mobile:: In the Evidence of BTN Mobile Banking Users in JABODETABEK - Easterina, Benedicta Samantha (Sekolah Tinggi Manajemen IPMI, 2024)
This research study the relationship and the impact of e-Service Quality on e-Satisfaction and loyalty in the BTN Mobile Banking users. This study uses modified dimensions of the E-SERVQUAL instrument to determine the e-SQ of BTN Mobile Banking service in JABODETABEK which are Personal Needs, Site Organization, User-friendliness and Efficiency. 103 respondents were involved in this study and the results showed E-SQ have significant impact to E-Satisfaction and Loyalty. Data analysis was performed using SEM-PLS. The limitations of this study are that the scope of the population is only in the special province of Jakarta, and the variables related to e-satisfaction are only emphasized from the perspective of user experience and interface while the research scope on e-satisfaction is very wide. The findings of this study show that in Internet banking, in addition to the technical and functional aspects of -SQ reflects the importance of contribution to e-satisfaction and e-loyalty. Keywords: E-Service Quality, Loyalty, Customer Satisfaction, E-Satisfaction